Brain Abscess Presenting as Postpartum Diabetes Insipidus - Silvia So-Haei Liu; Su-Chee Chen (Elsevier, 2004)
Objective: We report a rare case of brain abscess that was triggered during pregnancy in a patient with a history of head trauma and which led to postpartum diabetes insipidus. Case Reports: A 22-year-old primigravida woman had a history of traffic accident with subarachnoid hemorrhage 2 years prior to pregnancy. At 35 weeks' gestation, she was treated conservatively for stuffy nose, rhinorrhea, headaches, bilateral eyeball soreness and low-grade fever for 3 days. Cesarean section was performed at 37 weeks' gestation. Polyuria of 11,720 mL and hypernatremia were noted within 24 hours of delivery. She rapidly developed generalized seizures, with a Glasgow coma scale score of E1M4VET. Brain computed tomography scan and magnetic resonance imaging revealed a multiloculated, well-defined, ring-enhanced lesion in the left frontal lobe, which was compatible with a brain abscess. Surgical evacuation of the abscess was performed. However, hydrocephalus developed as a sequel of ventriculitis. She was discharged after 74 days of hospitalization with Omaya and V-P shunts remaining in place. Ten months after delivery, she had mild neurologic deficits and was under regular follow-up for rehabilitation of left hemiparesis. Conclusion: The diagnosis of brain abscess in this patient was masked by postpartum diabetes insipidus, which is an unusual manifestation. Symptoms and signs of brain abscess are nonspecific in the early stage and missed diagnosis is not uncommon. In conclusion, we reaffirm the importance of remarking on any past relevant information, and one should always be aware of any unresolved symptoms even though they may be nonspecific.